Performance Modulation for Back-Illuminated AlGaN Ultraviolet Avalanche Photodiodes Based on Multiplication Scaling - Qing Cai; Qian Li; Mo Li; Yin Tang; Jin Wang; Junjun Xue; Dunjun Chen; Hai Lu; Rong Zhang; Youdou Zheng (IEEE Photonics Journal, 2019)
Back-illuminated Al0.1Ga0.9N ultraviolet avalanche photodiodes (APDs) of various multiplication widths were fabricated on AlN templates with a separate absorption and multiplication structure. The impacts of an increased multiplication scale on a device performance were investigated. The avalanche breakdown voltage was found to increase as the multiplication layer thickness (MLT) increases. The APD with 230-nm-MLT achieved a superior maximum multiplication gain of 5.4 × 104, higher than that obtained in devices with 150-nm- and 300-nm-MLT. Theoretical simulations demonstrated that the critical electric field intensity in an avalanche region would decrease as the rising of MLT, indicating the modulating ability of multiplication scaling on the AlGaN APD performance. In addition, APDs fabricated on different AlN templates were employed to study the effects of crystalline quality on device properties.